Everolimus for pediatric patients with acute graft-versus-host disease after hematopoietic stem cell transplantation: A pilot study. Issue 44 (November 2017) - Chao, Yu-Hua; Chang, Yin-Chen; Wu, Han-Ping; Peng, Ching-Tien; Weng, Te-Fu; Wu, Kang-Hsi
Abstract : Abstract: Acute graft-versus-host disease (aGVHD) is a significant cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Due to the poor prognosis for patients not responding to first-line steroids treatment, improvements in aGVHD therapy are needed. Everolimus is a promising candidate that combines immunosuppressive properties with anti-neoplastic effects. Here, we retrospectively reviewed the efficacy of everolimus with steroids as primary treatment in 13 patients with grade II to grade IV aGVHD after HSCT. Among them, 12 (92.3%) had complete response to everolimus with steroids without additional immunosuppressive agents. The median duration of therapy was 76 days (range 20–110). Asymptomatic hypertriglyceridemia was the most common therapy complication (69.2%), but treatment interruption was not needed. Thrombotic microangiopathy was rare (7.7%), but can be quickly solved by stopping everolimus and cyclosporine treatment. Other toxicities were manageable. Two patients developed chronic GVHD (15.4%), limited in one and extensive in the other. The overall survival was 76.9% with a median follow-up of 3.4 years after HSCT (range 0.7–5.7). Accordingly, everolimus with steroids were feasible for patients with aGVHD after HSCT as primary treatment. Further large-scale studies are required.